Penerapan Asas Keadilan Terhadap Pengadaan Tanah Bagi Insfrastruktur Jalan Tol Trans Jawa - Wicaksono, Fikri Arif; Turisno, Bambang Eko (Notarius, 2023)
AbstractLand is increasing, for development. Land acquisition is acquired from land rights holders based compensation given to rights holders, accordance with the legal basis of Article 18 Law No. 5 1960. The aim is to analyze the compensation mechanism received by the Sambongsari Village residents applies principle of justice, obstacles faced by the community.occurs in the provision of compensation to solve the problem. Method is empirical juridical law research with reference to writing, direct observation for granting compensation certificates through deliberation, the form of determining compensation in compensation process must apply the principles of land acquisition, such as justice principle, good faith, legal certainty, propriety, well-being. Based on the study results, there’re no obstacles in compensation land acquisition for construction toll road in SambongsariVillage.Keywords: justice; land; procurement; infrastructure; lawsAbstrakKebutuhan lahan semakin meningkat, untuk pembangunan. Perolehan lahan diakuisisi dari pemegang hak atas tanah berdasarkan ganti kerugian yang diberikan kepada pemegang hak, sesuai landasan hukum Pasal 18 UU No. 5 Tahun 1960. Tujuan untuk mengetahui dan menganalisa apakah mekanisme ganti rugi yang diterima oleh warga Desa Sambongsari menerapkan prinsip keadilan, kendala yang terjadi pada pemberian ganti rugi dan cara penyelesaian masalahnya. Metode yang digunakan penelitian hukum yuridis empiris dengan mengacu pada tertulis, observasi langsung serta wawancara pemberian sertifikat ganti rugi melalui musyawarah, bentuk penetapan ganti rugi dalam proses pemberian ganti kerugian harus menerapkan asas pengadaan tanah, seperti asas keadilan, itikad baik, kepastian hukum, keseimbangan, kepatutan, dan  kesejahteraan. Berdasarkan hasil penelitian tidak ada kendala dalam proses ganti rugi pembebasan lahan pembangunan Tol Di Desa Sambongsari, Weleri Kabupaten Kendal.Kata kunci: keadilan; tanah; pengadaan; infrastruktur; hukum